New data on the hoverflies (Diptera: Syrphidae) of Serbia and Montenegro (Acta Entomologica Serbica, 2015)
The results of a survey on the hoverflies (Syrphidae) collected by the members of the pre-conference trip of the 5th International Symposium on Syrphidae are presented. Fieldwork took place from 8-22 June 2009 and involved 18 localities (12 in Serbia and 6 in Montenegro). The sites visited are described and short notes are given on some rare species. During the 15 days of fieldwork about 5600 specimens were collected representing 59 genera and 249 species. Seven species are recorded for the first time for Serbia: Epistrophe obscuripes, Merodon equestris, Merodon haemorrhoidalis, Microdon miki, Platycheirus angustipes, Rhingia borealis and Sphegina verecunda; and 19 species are recorded for the first time for Montenegro: Cheilosia crassiseta, Cheilosia lasiopa, Cheilosia pubera, Cheilosia rufimana, Cheilosia subpictipennis, Eumerus clavatus, Eumerus sogdianus Lejogaster tarsata, Merodon haemorrhoidalis, Merodon serrulatus, Myolepta dubia, Neoascia interrupta, Neoascia tenur, Platycheirus aurolateralis, Platycheirus occultus, Platycheirus tatricus, Sericomyia silentis, Sphaerophoria laurae and Trichopsomyia flavitarsis. The threat category of the endangered species according to VUJIĆ et al. (2001) is given for the species treated in the result section. For the records of new species additional data from the collection of Department of Biology an Ecology of Novi Sad, Serbia (FSUNS) are also presented. Some morphological characters useful to differentiate Anasymyia femorata ŠIMIĆ, 1987 from A. transfuga (LINNAEUS, 1758) and Merodon haemorrhoidalis SACK, 1913 from M. constans (ROSSI, 1794) are given. The female lectotype of M. haemorrhoidalis is studied and shows that it is a distinct species similar to M. constans.